Anterior tibial tendon transfer: a novel surgical proposal - Ramalho Júnior, Amancio; Generoso, Talissa Oliveira; Braga, Susana Reis; Pegoraro, Maurício; Camara Blumetti, Francesco (Journal of the Foot & Ankle, 2023)
Congenital equinovarus clubfoot is one of the most common congenital musculoskeletal deformities, and the treatment described by Ponseti is considered the gold standard; however, the recurrence rate can be significant. In cases of failed conservative treatment and persistent dynamic forefoot adduction and supination deformities, transfer of the anterior tibial tendon to the dorsolateral region of the foot may be indicated. In this paper, we present a novel surgical technique involving a double passage of the tendon through osseous tunnels and final fixation of the transferred tendon onto itself, ensuring optimal fixation and cost-effectiveness while mitigating complications associated with the conventional method. We advocate for adopting this novel technique as a treatment method for dynamic deformities resistant to non-surgical interventions for congenital clubfoot. Level of Evidence V; Therapeutic Studies; Expert Opinion.